Infection with Hepatitis C Virus among HIV-Infected Pregnant Women in Thailand. (27th January 2009) - Jamieson, Denise J.; Skunodom, Natapakwa; Chaowanachan, Thanyanan; Roongpisuthipong, Anuvat; Bower, William A.; Chotpitayasunondh, Tawee; Bhanich Supapol, Wendy; Kuhnert, Wendi L.; Siriwasin, Wimol; Wiener, Jeffrey; Chearskul, Sanay; McConnell, Michelle S.; et al.
Abstract : Objective . The purpose of this study was to describe the epidemiology of coinfection with hepatitis C virus (HCV) and HIV among a cohort of pregnant Thai women. Methods . Samples from 1771 pregnant women enrolled in three vertical transmission of HIV studies in Bangkok, Thailand, were tested for HCV. Results . Among HIV-infected pregnant women, HCV seroprevelance was 3.8% and the active HCV infection rate was 3.0%. Among HIV-uninfected pregnant women, 0.3% were HCV-infected. Intravenous drug use by the woman was the factor most strongly associated with HCV seropositivity. Among 48 infants tested for HCV who were born to HIV/HCV coinfected women, two infants were HCV infected for an HCV transmission rate of 4.2% (95% 0.51–14.25%). Conclusions . HCV seroprevalence and perinatal transmission rates were low among this Thai cohort of HIV-infected pregnant women.